Towards effective intervention and sector dialogue in occupational safety and health, 15-17 September 2004, Amsterdam. Proceedings (Den Haag, 2004)
"The main objective of this invitational conference is to convey the notion that there are many creative and effective ways in which companies, social partners, national and regional authorities can create a healthy and safe working environment. In particular different forms of sector dialogues at national and European level can be considered as (potentially) effective tools. "